Cyber Diplomacy (A Perspective From Indonesia - Australia Cyber Cooperation) - Ujang Priyono; Yoedhi Swastanto; Budi Pramono (CV. AFDIFAL MAJU BERKAH, 2023)
To address the increasing cyber threats, Indonesia is attempting to develop its cyber capabilities, one of which is collaboration with Australia. In practicing cyber diplomacy, the two countries employ different diplomatic models. Indonesia conducts cyber diplomacy through the Ministry of Foreign Affairs and the National Cyber and Crypto Agency (BSSN), whereas Australia conducts it through its cyber ambassador. This research will investigate how the Indonesian and Australian cyber diplomacy models work in cyber diplomacy using a descriptive-analytic approach. Based on the research results, even though Indonesia already has BSSN as the leading cybersecurity sector, Indonesia's foreign policy continues to emphasize the role of the Ministry of Foreign Affairs as the leading sector of foreign policy diplomacy. including dialogue or bilateral collaboration with other countries in the sphere of cybersecurity. This, of course, extends the coordinating framework for carrying out cyber cooperation. As a result, efforts by the Indonesian government are required to develop more effective cyber diplomacy policies in order to enhance Indonesia's cyber capabilities.